Vtubers and anime culture: a case study of Japanese learners in two public universities in Malaysia - Mamat, Roslina; Abdul Rashid, Roswati; Paee, Rokiah; Ahmad, Normah (Universidad Técnica de Manabí, 2022)
This study attempts to identify Malaysian youth's interest in anime culture and one of its subcultures, Virtual YouTubers (VTubers). Anime, manga and drama series count amongst the most popular and well-received types of Japanese popular culture since the 1990s, where their translation into various languages have rendered them globally renowned. A plethora of studies have been done on anime and manga globally. However, studies on its subculture, VTubers, an online platform that uses a digital avatar generated using computer graphics, are still scarce, particularly in the Malaysian context. A total of 104 respondents participated in an online survey conducted using Google Forms. The respondents comprised Japanese language students from two public universities in Malaysia. Some of the respondents are members of a Japanese Cultural Club from one of the universities. The survey was divided into three sections: respondents' background, respondents' interest in anime culture, and their interest in VTubers. The results showed that the most popular culture is anime, followed by manga, song and seiyuu (voice actor/actress). The most well-liked anime genre is fantasy, followed by humour, love stories (romance), and mystery. Most of the respondents knew the word "VTuber" from anime, friends, and internet platforms such as YouTube. The numbers proved that VTubers are a significant and famous product of Japanese culture among Japanese culture enthusiasts, and will likely gain extensive traction in the future.